(untitled) (Bangladesh Journal of Medical Science, 2026)
Objective To evaluate maternal and fetal outcomes in pregnancies with T2DM analyzing pharmacological treatments, lifestyle modifications, and postpartum care to identify effective interventions for managing complications and improving maternal and neonatal health outcomes. Materials and Methods A systematic review was conducted following PRISMA guidelines to synthesize evidence on Type 2 Diabetes Mellitus and pregnancy outcomes, complications, and management strategies. Comprehensive database searches (PubMed, Cochrane, DOAJ) using targeted keywords identified 5,068 records, narrowed to 17 highly relevant studies. Results and Discussion A systematic review of 17 studies, including 6 RCTs, explored maternal and fetal outcomes in pregnancies complicated by Type 2 Diabetes Mellitus and Gestational Diabetes Mellitus. Interventions included glycemic control (fasting glucose: 70- 95 mg/dL, postprandial: 100-140 mg/dL), metformin, insulin therapy, and lifestyle modifications like physical activity and dietary counseling. Maternal complications included preeclampsia (2-48%), gestational hypertension (8–21%), and excessive gestational weight gain. Fetal outcomes appeared with elevated threats of macrosomia (13%), preterm delivery (up to 85%), and neonatal hypoglycemia despite the fact that metformin decreased the chances of macrosomia and weight gain. Interventions done after delivery such as OGTT and weight control prevented the development of T2DM. Conclusion: The study provided evidence that Type 2 diabetes has repercussions on the results of pregnancy stressing on the need to control glycemia, the use of drugs, measures at the level of lifestyle and at the level of the postpartum period. BJMS, Vol. 25 No. 02 April’26 Page : 385-399